An Effect of the Sun, Normandy - Gustave Le Gray (Wikimedia Commons, 1856)
Notice iconographique issue de Wikimedia Commons. Titre: An Effect of the Sun, Normandy. Exploring the dramatic effects of sunlight, clouds, and water, Gustave Le Gray gained immediate recognition for his landmark photographs of the Mediterranean Sea and the English Channel taken between 1856 and 1858. At this time photographic emulsions were not equally sensitive to all colors of the spectrum, making it impossible to achieve a proper exposure for both sea and sky in a single image. Thus, for may of his seascapes Le Gray printed two negatives on a single sheet of paper, a technique called combination printing. One negative was taken of the water and the other of the sky. The overlap often apparent in such multiple negative images is not visible in this skillfully executed print.
Licence Public domain via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons; photographie